Students’ Perspectives on the Effectiveness of Problem-Based Learning in Enhancing Explanatory Text Comprehension and Production - Febrianti; Neta Dian Lestari; Januardi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study explores elementary students’ perceptions of the implementation of Problem-Based Learning (PBL) in explanatory text instruction. The research was conducted at SD Negeri 234 Palembang and involved 24 sixth-grade students selected through purposive sampling. A descriptive qualitative approach was employed to gain an in-depth understanding of students’ learning experiences. Data were collected through classroom observations, semi-structured interviews, and questionnaires. The data were analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. To ensure the credibility and trustworthiness of the findings, methodological triangulation was applied. The findings demonstrate that students generally perceived the PBL approach positively. They reported that learning became more engaging, meaningful, and interactive compared with traditional teacher-centered instruction. The implementation of PBL encouraged active participation in discussions, increased students’ confidence in expressing ideas, and strengthened collaboration among peers during problem-solving activities. Furthermore, the use of real-world problems helped students better understand explanatory text structures and identify cause-and-effect relationships within texts. The learning process also stimulated critical thinking and supported deeper comprehension of instructional content. Overall, the study concludes that PBL is an effective pedagogical approach for explanatory text learning at the elementary school level, fostering student engagement, collaborative learning, and improved conceptual understanding.